Pengembangan Modul Berbasis Discovery Learning pada Mata Pelajaran Pemeliharaan Mesin dan Kendaraan Ringan Kelas XI SMK Judul Jurnal dalam Bahasa Indonesia - Alhadi, Hafizh; Wakhinuddin, Wakhinuddin (Universitas Negeri Padang, 2024)
This study aims to develop a Discovery Learning-based module in the subject of Maintenance of Engines and Light Vehicles, with a focus on Electronic Fuel Injection (EFI) System Maintenance. The research involves module testing through expert assessment and limited trials with the participation of 30 students from the 11th grade of Light Vehicle Engineering. The module development follows the Plomp model, through the preliminary investigation and prototype phases. The preliminary investigation phase revealed a variety of teaching methods in Maintenance of Engines and Light Vehicles, including lectures and practicals, but their effectiveness was limited. The existing teaching materials were inadequate, unclear, and lacked comprehensive information. Interviews with students indicated difficulties in comprehending the concepts related to the subject. Therefore, the need for an engaging and informative module was identified. The module underwent validation by experts, including content specialists, educators, and graphic designers. The validation process resulted in high scores. Practicality evaluation was conducted gradually, involving small-group and large-group evaluations. The results showed a high level of practicality in terms of ease of use, time efficiency, and attractiveness for students. Further evaluation focused on module effectiveness. Pre-tests and post-tests were conducted to measure cognitive, affective, and psychomotor learning outcomes. The results demonstrated significant improvements in cognitive and psychomotor skills, as well as moderate improvements in affective aspects. These findings confirm that the Discovery Learning-based module effectively enhances students' learning outcomes in the subject of Maintenance of Engines and Light Vehicles, particularly concerning the EFI system. In conclusion, the developed module proves to be effective in enhancing students' learning outcomes in the subject of Maintenance of Engines and Light Vehicles, particularly in relation to the EFI system.